Electrophysiological response to visual symmetry: Effects of the number of symmetry axes. (23rd January 2022) - Wang, Meng; Wu, Fengxia; van Tonder, Gert; Wu, Qiong; Feng, Yang; Yu, Yiyang; Yang, Jiajia; Takahashi, Satoshi; Ejima, Yoshimichi; Wu, Jinglong
Highlights: Symmetry axis processing occurred not only in the bilateral posterior areas but also in the frontal and central areas. Increased amplitude with an increasing number of symmetry axes. Reduced latency with an increasing number of symmetry axes. The latency reduction with symmetry axes was evident over right hemisphere. Abstract: The symmetry axes of a stimulus are a critical determinant of visual perception. Although much is known about the effects of a single symmetry axis on perception, the effects of multiple symmetry axes are still poorly understood. Here, we investigated the influence of the number of symmetry axes on brain activity using event-related potentials (ERPs). Our results showed that altering the number of symmetry axes affects both the amplitude and the latency of ERPs. Specifically, the amplitude of ERP components increased as the number of symmetry axes increased, starting at the N1 (165–175 ms) component and lasting until the P2 (230–250 ms) component in the bilateral posterior areas and until the N2 (340 ms) component in the frontal-central areas. Importantly, the latency of ERP components was reduced when the number of symmetry axes increased, starting at the N1 in the right posterior area and lasting until the P2 component in the bilateral posterior areas. The temporal and spatial differences in these effects imply that activity related to symmetry axes gradually changes throughout the ventral visual streams in the human brain.